The role of urine albumin creatinine ratio and serum β2 microglobulin as biomarkers of chronic kidney disease (Universa Medicina, 2019)
BACKGROUNDChronic kidney disease (CKD) is an increasing burden on individuals and on the healthcare system. The need to identify more sensitive and specific markers of CKD cannot be overemphasized to facilitate detection and appropriate intervention. β2 microglobulin is one of such markers of CKD. The aim of this study was to investigate the sensitivities and specificities of serum β2 microglobulin and major biochemical markers of CKD, namely creatinine and urine albumin. METHODSThis was a hospital-based cross-sectional study involving 124 subjects with CKD and 124 healthy controls. Participants were categorized in two groups : group 1 the CKD based on persistent reduction in GFR